Detection of antifungal compounds in Arabidopsis thaliana and brassica oleracea by thin layer chromatography . - K.P. Chong; J.W. Mansfield; M.H. Bennet; J.F. Rossiter (ASEAN Journal on Science and Technology for Development, 2006)
Thin Layer Chromatography (TLC) was applied to detect antifungal compounds both in Arabidopsis thaliana and Brassica oleracea after elicited by various biotic and abiotic elicitors.From TLC bioassays the only strong zone of inhibition detected after challenged by Pseudomonas syringae pv.maculicola was from Arabidopsis tissue and later confirmed by spectrophotometry as camalexin but no corresponding phytoalexin was found in broccoli leaf.